Tinjauan Hukum Ekonomi Syariah Tentang Bagi Hasil Berdasarkan Keuntungan Dan Resiko Di Peternakan Ayam Petelur Qiana Farm - Sunarsa, Sasa; Al Busyaeri, Moch Fauzan (Jurnal Hukum Ekonomi Syariah, 2024)
Problems that often occur in animal husbandry are failures in the management system and division of tasks. In business, if financial management is not managed well and clearly, there will be confusion in management, and it is also prone to fraud. To avoid fraud and opacity, finances must be managed well with transparency in the system of profit sharing among livestock managers. The problem formulation in this research is: 1). What is the cultivation process and mechanism at the Qiana Farm laying hen farm?, 2). What is the review of sharia economic law regarding the profit sharing pattern based on profits and risks in the Qiana Farm laying hen farm? Then the aim is to find out about the process and mechanism of the profit sharing pattern based on profits and risks in the Qiana Farm laying hen farm, and to analyze the review of sharia economic law regarding the profit sharing pattern of the Qiana Farm laying hen farm. The method used by the author is field research, and this research also uses descriptive methods and analysis with a qualitative approach. The results of the research can be concluded that from the profit sharing pattern of Qiana Farm's laying hen farming in terms of sharia economic law using a Musyarakah Agreement (Syirkah Mufawadhah), the percentage distribution of profits in the laying hen business is 50:50, always applying justice and losses are borne jointly. The same.  Keywords: Sharia Economic Law; Profit sharing; Laying Hens